Nanomechanics Theory and Application - Vakhrushev, Alexander V. (IntechOpen, 2021)
This book covers a wide range of research in the field of nanomechanics. Chapters address nanomodification of the surface of solids, a refined method for calculating nanomaterials with cracks, the formation of nanocomposites based on nanoparticles, and methods for the experimental determination of the mechanical parameters of nanomaterials. The book is a useful resource for engineers, technologists, and researchers interested in methods of nanomechanics and the application of advanced nanomaterials with complex behavior.